Comparison of conventional awake extubation with endotracheal tube – laryngeal mask airway exchange extubation for evaluation of respiratory and hemodynamic parameters during emergence in neurosurgical patients - Vyas, Amit; Singh Baghel, Kamalraj; Nandurkar, Pawan; Tripathi, Sonali (Asian Journal of Medical Sciences, 2022)
Background: Emergence from general anesthesia and tracheal extubation may be associated with tremendous physiological and metabolic stress in patients which could be major concern for the anesthesiologist in patients especially with neurosurgical patients. Aims and Objectives: The study was designed to find a novel method to achieving a smooth extubation in neurosurgery by compare the respiratory complications and hemodynamic stress response between conventional awake extubation of an endotracheal tube (ETT) and that following exchange extubation of ETT using a laryngeal mask airway (LMA) in craniotomy surgeries. Materials and Methods: A total of 60 patients of American Society of Anesthesiologists physical status I and II between ages 18 and 60 years undergoing neurosurgery were evaluated for respiratory events such as bucking, coughing, desaturation, and hemodynamic changes due to sympathetic stimulation such as tachycardia, hypertension, and any other complications that have occurred in any of the two extubation methods. Results: In Group A, 86.67% patients have shown significant events of bucking and coughing while desaturation events were comparable between two groups. Manipulation events, that is, chin lift and jaw thrust had to perform in 66.67% and 21.67%, respectively, in patients of Group A compared to only 03.33% patients in Group L. (P<0.05). In Group A, 97.33% patients shown tachycardia compared to 30% in Group L where only 30%. Similarly, mean arterial pressure after extubation found to be significantly high in 63.33% of the patients in Group A with 63.33% as compared to13.33% of patients in Group L (P<0.05). Conclusion: ETT/LMA exchange is the most effective technique for achieving the clinical endpoints of the study, that is, prevention of emergence hypertension and respiratory complications compared to awake extubation methods. The exchange of ETT with LMA in deeper plane of anesthesia significantly reduces emergence related the hemodynamic and respiratory unwonted events.